Virtue Ethics and Professional Journalism - Quinn, Aaron (Springer International Publishing, 2018)
This book examines the moral role of news media practitioners and organizations, and applies a modified philosophical account of Virtue Ethics as a framework for the role of journalists-and journalism organizations-in public life. It shows how journalists and news organizations that adopt an aim towards professional excellence (virtue) by putting a premium on investigative journalism-with both large and small measures depending on the nature of the reporting-can achieve lofty professional goals under modern deadlines. The news media, both electronic and traditional, are imperative to an informed public, and an informed public is critical to a properly functioning cross-section of social, government and corporate domains. The book emphasizes the virtues of justice and integrity as foundational to professional practice. It examines the modern ethical challenges presented by organizations ranging from online upstarts to massive media conglomerates, each that have economic challenges that can inhibit professional excellence through corruption or corrosion. The author applies his account of virtue-bolstered by suggestions for complementary reforms in education and regulation-to improve an ethically challenged industry as it undergoes significant technological change.